Retropharyngeal abscess coinfected with and after rhinoviral infection in a 1-month-old infant - Jeong Hee Shin; Se In Sung; Jin Kyu Kim; Ji Mi Jung; Eun Sun Kim; Soo Han Choi; Yae Jean Kim; Kang Mo Ahn; Yun Sil Chang; Won Soon Park (Korean Pediatric Society, 2013)
A retropharyngeal abscess is a rare disease entity in young infants but can develop after nasopharyngeal viral infection. Group B Streptococcus and Staphylococcus aureus are the most common pathogens in young infants, however, Mycobacterium tuberculosis is very rare. We report the case of retropharyngeal abscess and coinfection with S. aureus and M. tuberculosis in a very young infant presenting with respiratory symptoms due to upper airway obstruction. Usually tuberculous retropharyngeal abscesses are caused by the direct invasion of the bacteria from the spine via anterior longitudinal ligament of the spine. However, in this case, no associated spinal disease was observed.